Mental Health Effects on Adolescents due to Limited Social Interaction - Singaporewala, Fatema Yusuf; Bernhardt, Grisilda Vidya; Shivappa, Pooja (Migration Letters, 2024)
Social interaction is a fundamental human need, crucial for mental well-being and emotional development. Adolescence, a period marked by increased sensitivity to peer influence, is particularly affected by social interactions. We proposed a retrospective cross-sectional design employing adolescents aged 16-18 using a structured questionnaire comprising 38 items.The questionnaire covered demographics, anxiety, depression, stress, emotional regulation, daily life effects, and media exposure. Data analysis involved descriptive statistics, Pearson correlation coefficients and independent sample t-tests using SPSS software. Our study found that anxiety levels stood at 41%, depression at 37%, and stress at 91% among adolescents during the period of denied social interaction. Participants who engaged in cognitive reappraisal and expressive suppression had higher emotional regulation scores. We found a correlation among anxiety, depression, stress and emotional regulation. It also revealed significant hindrances in social interactions, education, and extracurricular activities, all vital for adolescent mental health. Mental health in adolescents is just as vital as their physical health in shaping them into self-assured, independent adults. This study highlights the adverse consequences of DSI on adolescent mental well-being and underscores the importance of addressing these issues in future public health planning. Highlights The research showed a significant rise in mental health issues among adolescents during limited social Interaction. Based on our study, anxiety, depression, and stress increased in adolescents during the period of denied social interaction. Insufficient social interaction, encompassing issues in mingling with friends and attending school, correlated with elevated depression, anxiety, and stress rates in adolescents thus social connections are vital for sustaining mental well-being. A significant portion of adolescents engaged in emotional regulation techniques. These techniques were associated with their ability to manage and express emotions. It emphasizes the need for supportive measures and responsible media usage to mitigate the adverse effects of social isolation on the mental well-being of young individuals.